Polymer microsphere-assisted synthesis of lithium-rich cathode with improved electrochemical performance. Issue 4 (March 2016) - Ma, Shaomeng; Hou, Xianhua; Huang, Yanling; Li, Changming; Hu, Shejun; Lam, Kwok-ho
Abstract: The Li-rich layered cathode material Li1.165 Mn0.501 Ni0.167 Co0.167 O2 with porous structure has been successfully synthesized through a facile co-precipitation approach followed with a high-temperature calcination treatment, adopting polymer microsphere (PSA) as a template and conductive agent. The PSA-assisted Li1.165 Mn0.501 Ni0.167 Co0.167 O2 composite exhibits remarkably improved cycling stability and rate capability compared with the bare composite. It delivers a high initial discharge capacity of 267.0 mA h g −1 at 0.1 C (1 C=250 mA g −1 ) between 2.0 V and 4.65 V. A discharge capacity of 214.9 mA h g −1 is still obtained after 100 cycles. Furthermore, the diffusion coefficients of Li + investigated by the cyclic voltammetry technique are approximately 10 −15 –10 −14  cm 2  s −1 . Such outstanding performance is mainly ascribed to: on one hand, the carbon residue of PSA after being calcined at high temperature contributes to enhance the electronic conductivity of the electrode and alleviates the volume changes during the Li + -insertion/extraction, leading to an improved rate capability; on the other hand, the unique porous structure and small particle size are conductive to increase the exposed electrochemical active surface, shorten Li + diffusion distance and thus enhance the lithium storage capacity.